Postoperative dry eye after ophthalmic surgery - Jacobi, Christina (Spektrum der Augenheilkunde, 2021)
Dry eye is common after ophthalmic surgery. In addition to refractive surgery, this particularly applies to cataract and glaucoma surgery. Pathogenetically, damage to the corneal nerves with the occurrence of neurotrophic keratopathy plays a decisive role. The duration of postoperative dry eye varies individually and depends on the surgical procedure. While regression usually takes place over 3 months after cataract surgery, the duration after refractive surgery is usually 6 months and can persist in up to 40% of patients. After trabeculectomy, dry eye occurs in approximately 40% of patients. For the occurrence, persistence and severity of postoperative dry eye, it is essential to detect and treat asymptomatic forms of meibomian gland dysfunction and all forms of dry eye both preoperatively and postoperatively. This is the only way to achieve an optimal postoperative result with high patient satisfaction.
CRIS-Team WoS Importer:2021-09-03